KEBERHASILAN USAHA DITINJAU DARI BALANCE SCORECARD - OKTAVINI, RAHAYU WANDA; ANIMAH, ANIMAH; MARIADI, YUSLI (GANEC SWARA, 2024)
This research aims to develop a system for measuring the organizational performance of real estate development companies based on the concept of Balance Scorecard (BSC) and Analytical Hierarchy Process (AHP) at PT. Meka Asia Property. This research is a type of quantitative research with a descriptive approach. This research uses primary data and secondary data with several data collection methods including interviews, questionnaires, literature studies and documentation. The research results show that PT. Meka Asia Properti has performed well. Judging from the average score obtained, it is 3.7 which is included in "Good Company Performance". From the AHP results, the weight of each perspective is 0.64 for the customer perspective which shows the highest priority, and than the internal business process perspective at 0.21, then the financial perspective with a weight of 0.11, then the last one is 0 .04 for the growth and learning perspective which has the lowest weight